Peningkatkan Jumlah Produksi Pengasapan Ikan Di Desa Campurejo, Kecamatan Panceng, Gresik - Novi Indah Riani; Aini Lostari; Miftahul Ulum; Moh. Yusril Fahmi (CV. Multi Kreasi Media, 2023)
The biggest potential possessed by Campurejo Village, Panceng-Gresik District is its natural resources which are close to the sea. This makes the majority of its peoples work as fishermen. The fish caught are usually sold directly in the market or processed into smoked fish. The smoking process is carried out conventionally. This can make the amount of smoked fish production limited each day. This activity aims to provide a solution to increasing the amount of smoked fish production produced every day by using more modern machines. After the machine has been made, a machine use workshop is held with the aim of providing information regarding the use and advantages of this machine. This machine has a capacity of 14 Watts, with an AC current source and a roasting time of 30 minutes to produce 5 kg of smoked fish.